2013
DOI: 10.1016/j.diii.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI features of granulomatous prostatitis and tubercular prostate abscess

Abstract: The authors report the diffusion and contrast-enhanced MRI appearance of five cases of granulomatous prostatitis (GP), non-specific (two cases) and infectious post-Bacillus Calmette-Guerin (BCG) therapy (three cases, with a tubercular abscess in two of them). All patients had raising PSA levels and abnormal DRE. History of BCG therapy or acute prostatitis was present in four patients. Multiparametric MRI (T2W-MRI, DW-MRI and DCE-MRI) was performed before biopsies. Diagnosis was confirmed by TRUS-guided biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 14 publications
1
55
2
Order By: Relevance
“…Another recent report of 5 patients found a slight decrease in mean Apparent Diffusion Coefficients (ADC) derived from diffusion weighted MRI for CGP versus prostate cancer with moderate dynamic contrast enhancement (DCE) of CGP lesions, again overlapping with PCa. 8 MR spectroscopic imaging reports have included even fewer patients and have thus been unable to describe conclusive findings. 9 For these reasons, prostate biopsy remains the only definitive method for distinguishing CGP from PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report of 5 patients found a slight decrease in mean Apparent Diffusion Coefficients (ADC) derived from diffusion weighted MRI for CGP versus prostate cancer with moderate dynamic contrast enhancement (DCE) of CGP lesions, again overlapping with PCa. 8 MR spectroscopic imaging reports have included even fewer patients and have thus been unable to describe conclusive findings. 9 For these reasons, prostate biopsy remains the only definitive method for distinguishing CGP from PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In the peripheral zone, it appears as an area of hypointensity on T2-weighted images associated with diffusion restriction and with moderate or marked enhancement on DCE images. In necrotic granulomatous prostatitis, central necrosis (caseation) has high signal intensity on T2-weighted images, with focal hyperintensity on high- b -value images, marked diffusion restriction, and total lack of enhancement on DCE images (45) (Fig 7). Florid granulomatous prostatitis may demonstrate extraprostatic extension.…”
Section: Mimics Of Prostate Carcinoma At Mr Imagingmentioning
confidence: 99%
“…Prediposing risk factors that should raise the possibility of mycobacterial granulomatous prostatitis include history of tuberculosis infection, bacillus Calmette-Guérin therapy, and immunosuppressive state (46,47). With treatment, the swelling of the prostate reduces and the caseous abscess cavity resolves (45). There may be residual fibrosis and calcification based on previously reported computed tomographic features of mycobacterial granulomatous prostatitis (48,49).…”
Section: Mimics Of Prostate Carcinoma At Mr Imagingmentioning
confidence: 99%
“…The MR imaging features of BCG-induced GP have been reported to be nonspecific (9, 11). In general, BCG-induced GP shows a tumor-like appearance with hypo-signal intensity on T2WI, similar to that of prostate cancer, in foci that involve the peripheral zone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bour et al (11) reported that repeat imaging after 1 year of antituberculous treatment results in a return to normal appearance of the prostate gland with no detectable residual cavity.…”
Section: Discussionmentioning
confidence: 99%